Integrative and complementary health practices in the nurses’ action of primary health care. - Mildemberg, Rafaela; Paes, Marcio Roberto; dos Santos, Benedita Almeida; Dalmolin, Indiara Sartori; Brusamarello, Tatiana (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2023)
Objective: to analyze the knowledge and use of integrative and complementary practices in the work of nurses in Primary Health Care. Method: a cross-sectional study carried out in 85 Basic Health Units in Curitiba-PR in 2021. The sample consisted of 195 recruits recruited using the Snowball technique. The were confirmed by means of an electronic data selection instrument and methods by electronic descriptive data methods. Results: 43 (22.1%) of the participants use integrative and complementary practices (PIC) in care, and 31 (15.9%) reported having training in some modality. The use of 17 PIC modalities was identified, 33 (47.8%) in auriculotherapy and 7 (10.1%) in reiki. The Ranking item on the theoretical knowledge of the average participants on the topic was >3.89, demonstrating agreement with the statements. About how participants experience the PIC, due to the recognition of nursing practices. Conclusion: the study contributes to the characterization of nurses’ performance in primary care based on integrative and complementary practices. The findings serve as a subsidy for professionals and managers to identify gaps in knowledge, in action, as well as in the management of primary care health services in order to strengthen the professional autonomy of those who use these practices in care.